MAMPUKAH RELIGIUSITY MEMODERASI PENGARUH MACHIAVELLIAN TERHADAP TAX EVASION - Dwi Suci Rahma Danti; Rachmawati Meita Oktaviani (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
This study aims to study the influence of machiavellian and religiosity as a moderating variable on tax evasion in this study are all individual taxpayers registered in the North West Java KPP Pratama. The number of samples used in this study were 100 respondents from 101,055 taxpayers received. The sample selection technique uses random purposive sampling. Data collection in this method using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that machiavellian had a positive effect on tax evasion, religiosity had a negative impact on tax evasion and that religion did not moderate the relationship of positive machiavellian influence on tax evasion. Keywords: machiavellian, relogiusity, tax evasion